Traditional Games Activities to Develop Fundamental Movement Skills of Elementary School Students - Supriadi, Dedi (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
This study was aimed at recognizing the effect of traditional games on the elementary students’ fundamental movement skills. This study employed the experimental method with one-group pretest-posttest design. The population of this study were the 3rd grade students consisting of 84 students as the sample. In determining the research sample, the researcher administered the total sampling technique. To discover the effect, the sample received treatments before the post-test. The treatments were conducted for 8 weeks with 2 hours per meeting. The traditional games included in this study were Galasin, Gatrik, Bebentengan, Kasti, and Penggaris Games. This study used the second edition of Test of Gross Motor Development (TGMD-2) as its instrument. The data were then analyzed and processed by using paired sample t-test with SPSS 21. This study revealed that the traditional games had significant effect on the students’ fundamental movement skills. The traditional games could be used as a mean of enhancing fundamental movement. AbstrakTujuan penelitian ini adalah untuk mengetahui pengaruh permainan tradisional terhadap keterampilan gerak fundamental siswa sekolah dasar. Penelitian ini menggunakan metode eksperimen dengan the one group pretest-posttest design. Populasi penelitian ini adalah siswa Sekolah Dasar kelas 3 dengan sampel sebanyak 84 siswa. Teknik pengambilan sampel menggunakan total sampling. Perlakuan dilakukan selama 8 minggu dengan 2 jam setiap pertemuannnya. Permainan tradisional yang digunakan yaitu Galasin, Gatrik, Bebentengan, Kasti, Permainan Penggaris. Instrument yang digunakan dalam penelitian ini adalah Test of Gross Motor Development (TGMD) second edition. Analisis dan pengolahan data menggunakan SPPS 21 dengan paired sample t-test. Hasil penelitian menunjukan terdapat pengaruh yang signifikan dari permainan tradisional terhadap keterampilan gerak fundamental siswa sekolah dasar. Permainan tradisional dapat dijadikan salah satu jalan dalam mengembangkan gerak fundamental.